2021
DOI: 10.1080/19390211.2021.1926392
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of L-Citrulline on Blood-Lactate Removal Kinetics Following Maximal-Effort Exercise

Abstract: The accumulation of lactate in muscle and blood during high-intensity exercise is negatively correlated with the duration exercise can be sustained. Removal of lactate is a key component of acute recovery between consecutive bouts of such exercise. Low-intensity exercise enhances recovery by accelerating lactate turnover in metabolically active tissues, largely mediated by blood flow to these tissues. Therefore, the purpose of this research was to clarify if L-citrulline, a nutritional supplement purported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As lactate clearance relies on oxidative capacity, it is plausible that the reported effects of supplementation on aerobic metabolism could positively impact on athletes’ oxidative capacity and therefore be an indirect sign of improved aerobic performance. Some studies have also reported lower blood lactate concentrations after CIT supplementation (Rhim et al 2020 ; Divito et al 2022 ), but the literature regarding BR supplements remains unclear. In fact, potential mechanisms related to lower blood lactate values after CIT supplementation might be related to enhanced aerobic pathway, as reported for instance by higher levels of plasma lactate dehydrogenase enzyme (Rhim et al 2020 ), which could be in accordance to previously identified effects of NO-related supplements such as BR.…”
Section: Discussionmentioning
confidence: 99%
“…As lactate clearance relies on oxidative capacity, it is plausible that the reported effects of supplementation on aerobic metabolism could positively impact on athletes’ oxidative capacity and therefore be an indirect sign of improved aerobic performance. Some studies have also reported lower blood lactate concentrations after CIT supplementation (Rhim et al 2020 ; Divito et al 2022 ), but the literature regarding BR supplements remains unclear. In fact, potential mechanisms related to lower blood lactate values after CIT supplementation might be related to enhanced aerobic pathway, as reported for instance by higher levels of plasma lactate dehydrogenase enzyme (Rhim et al 2020 ), which could be in accordance to previously identified effects of NO-related supplements such as BR.…”
Section: Discussionmentioning
confidence: 99%
“…The ATP yield from glycolysis is highest in exhaustive short-term exercise (i.e., 400 meters sprint), which increases muscle acidosis (measured by blood lactate) (Hirvonen, Nummela, Rusko, Rehunen, & Härkönen, 1992). In addition, this level of acidosis attains an individual maximum (Hirvonen, et al, 1992) and stays elevated for 3-to-5-min post-exercise (Divito, McLaughlin, & Jacobs, 2021).…”
Section: Discussionmentioning
confidence: 99%